2018
DOI: 10.12659/msm.908616
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Showed Therapeutic Effects on Sepsis-Induced Acute Lung Injury in Rats by Inhibiting Endoplasmic Reticulum Stress Protein Kinase RNA-Like Endoplasmic Reticulum Kinase (PERK) Signaling-Induced Apoptosis of Pulmonary Microvascular Endothelial Cells

Abstract: BackgroundAcute lung injury (ALI) is a life-threatening complication of sepsis. Tetramethylpyrazine (TMP) has been used in the clinical treatment of vascular diseases. The aim of this study was to investigate the therapeutic effects and possible involved mechanisms on ALI.Material/MethodsCecal ligation and puncture (CLP) was used to establish a sepsis model in rats. TMP at various dosages were administrated to rats using a intragastric method. Animal survival rate was calculated. The lung functions were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…It was reported that the endoplasmic reticulum (ER) stress-inducible transcription factor CHOP induced cell death and was an important factor in the pathogenesis of different disease mouse models [ 19 , 38 , 39 , 40 , 41 , 42 ]. To investigate the effect of Mito-T on the expression of CHOP after APAP-induced liver injury, Mito-T (20 mg/kg, i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the endoplasmic reticulum (ER) stress-inducible transcription factor CHOP induced cell death and was an important factor in the pathogenesis of different disease mouse models [ 19 , 38 , 39 , 40 , 41 , 42 ]. To investigate the effect of Mito-T on the expression of CHOP after APAP-induced liver injury, Mito-T (20 mg/kg, i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…A large amount of bacteria and endotoxins in the intestinal tract invade the blood circulation through the portal vein and lymphatic system, causing intestinal infection, endotoxemia, and the activation of cytotoxic pathways, which eventually lead to multiple organ dysfunction syndrome. Lung injury often occurs early and develops fast, which is one of the most direct causes of death in patients with sepsis …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that biomarkers in the plasma and BALF can be used to evaluate ALI severity ( 37 ). Decreased lung W/D ratio and protein content in BALF, together with increased PaO 2 , are indicators of attenuated ALI ( 38 , 39 ). According to the findings of the present study, ATRA markedly increased PaO 2 in arterial blood and reduced the protein content in BALF and lung W/D ratio in ALI rats, along with effectively alleviating pathological lung injury.…”
Section: Discussionmentioning
confidence: 99%